CYP2B6 genotypes and early efavirenz-based HIV treatment outcomes in Botswana. (24th September 2017) - Gross, Robert; Bellamy, Scarlett L.; Ratshaa, Bakgaki; Han, Xiaoyan; Vujkovic, Marijana; Aplenc, Richard; Steenhoff, Andrew P.; Mosepele, Mosepele; Moorthy, Ganesh; Zuppa, Athena F.; Strom, Brian L.; Bisson, Gregory P.
Abstract : Objectives: To determine the association between cytochrome p450 2B6 genotypes and efavirenz-based HIV treatment outcomes. Design: Observational cohort study of HIV-infected adults initiating efavirenz-based regimens in Botswana. Methods: The primary endpoint was a composite of death or loss to care or HIV RNA more than 25 copies/ml at 6 months. CYP2B6 516G>T and 983T>C genotyping was done with Taqman Open Array platform. Adverse experiences were measured by using the Subject Experience Questionnaire. Metabolism alleles were included in logistic regression models of the composite endpoint. Results: A total of 801 individuals included 406 (51%) men, median age 37 years, median baseline CD4 + cell count 195 cells/μl, and plasma HIV RNA 4.9 log10 copies/ml. 288 (36%) reached the endpoint, including 34 (4%) deaths, 151 (19%) lost to care, 11 (1%) lost to the study, but alive and in care, and 92 (11%) with plasma HIV RNA more than 25 copies/ml. Metabolism variant alleles were common with 396 (49%) intermediate and 192 (24%) slow metabolizers. There were no statistically significant associations between metabolism and treatment endpoints. However, slower metabolism was associated with fewer adverse experiences. Conclusion: Slow metabolism alleles were associated with lower efavirenz clearance but not any of the treatment endpoints. Slow efavirenz metabolism did not exacerbate central nervous system toxicity. These results should allay concern that slow efavirenz metabolism adversely impacts individuals in sub-Saharan African settings in which these alleles are common. Abstract : Supplemental Digital Content is available in the text